2007
DOI: 10.1016/j.immuni.2007.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B and Perforin Are Important for Regulatory T Cell-Mediated Suppression of Tumor Clearance

Abstract: Granzyme B is important for the ability of NK cells and CD8(+) T cells to kill their targets. However, we showed here that granzyme B-deficient mice clear both allogeneic and syngeneic tumor cell lines more efficiently than do wild-type (WT) mice. To determine whether regulatory T (Treg) cells utilize granzyme B to suppress immune responses against these tumors, we examined the expression and function of granzyme B in Treg cells. Granzyme B was not expressed in naive Treg cells but was highly expressed in 5%-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
585
3
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 779 publications
(615 citation statements)
references
References 45 publications
18
585
3
9
Order By: Relevance
“…Ex vivo evaluation of in vivo activated NK and T cells also showed that tumor-activated regulatory T cells can cause the death of NK and CD8 þ T cells in a granzyme B-and/or perforin-dependent pattern. 25 The studies described here suggest that regulatory T cells can suppress the ability of CD8 þ T cells to clear tumors. Our data novelly showed that not only is the granzymeperforin pathway important for the function of NK and CD8 þ T cells, but it may reciprocally be used by regulatory T cells to restrain the activity of these cells.…”
Section: Regulatory T Cells In Endometrial Cancer/chang Et Almentioning
confidence: 70%
See 2 more Smart Citations
“…Ex vivo evaluation of in vivo activated NK and T cells also showed that tumor-activated regulatory T cells can cause the death of NK and CD8 þ T cells in a granzyme B-and/or perforin-dependent pattern. 25 The studies described here suggest that regulatory T cells can suppress the ability of CD8 þ T cells to clear tumors. Our data novelly showed that not only is the granzymeperforin pathway important for the function of NK and CD8 þ T cells, but it may reciprocally be used by regulatory T cells to restrain the activity of these cells.…”
Section: Regulatory T Cells In Endometrial Cancer/chang Et Almentioning
confidence: 70%
“…Regulatory T cells derived from the tumor environment could induce natural killer (NK) and CD8 þ T cell death in a granzyme B-and perforin-dependent fashion. 25 Granzyme B and perforin are therefore relevant for regulatory T cell-mediated suppression of tumor clearance in vivo. Grossman et al demonstrated that activated human regulatory T cells can use the perforin-granzyme pathway to kill a variety of autologous immune cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…67 Interestingly, CD4 þ Foxp3 þ Treg-mediated inactivation of tumor-specific CTLs in the tumor microenvironment has been shown to be contact dependent and reliant on perforin and granzyme B to the extent that mice lacking this granzyme clear transplanted tumor cell lines more efficiently than do wild-type mice. 68 Therefore, in some settings, a tumor may turn the tables on the immune system by using the destructive power of the perforin/granzyme pathway to its advantage. However, more evidence is required before this concept can be fully embraced.…”
Section: The Perforin-granzyme Pathway In Cancer Preventionmentioning
confidence: 99%
“…There are four mechanisms by which T regs suppress responder T cells [20][21][22][23][24]. First, T regs secrete inhibitory cytokines such as interleukin (IL)-35, IL-10 and transforming growth factor (TGF)-b to inhibit T cells directly.…”
Section: Introductionmentioning
confidence: 99%